Development of a new Sonovue™ contrast‐enhanced ultrasound approach reveals temporal and age‐related features of muscle microvascular responses to feeding. Issue 5 (27th October 2013) - Mitchell, William Kyle; Phillips, Bethan E.; Williams, John P.; Rankin, Debbie; Smith, Kenneth; Lund, Jonathan N.; Atherton, Philip J.
Abstract: Compromised limb blood flow in aging may contribute to the development of sarcopenia, frailty, and the metabolic syndrome. We developed a novel contrast‐enhanced ultrasound technique using Sonovue™ to characterize muscle microvasculature responses to an oral feeding stimulus (15 g essential amino acids) in young (~20 years) and older (~70 years) men. Intensity‐time replenishment curves were made via an ultrasound probe "fixed" over the quadriceps, with intermittent high mechanical index destruction of microbubbles within muscle vasculature. This permitted real‐time measures of microvascular blood volume (MBV), microvascular flow velocity (MFV) and their product, microvascular blood flow (MBF). Leg blood flow (LBF) was measured by Doppler and insulin by enzyme‐linked immunosorbent assay. Steady‐state contrast concentrations needed for comparison between different physiological states were achieved <150 sec from commencing Sonovue™ infusion, and MFV and MBV measurements were completed <120 sec thereafter. Interindividual coefficients of variation in MBV and MFV were 35–40%, ( N  = 36). Younger men ( N  = 6) exhibited biphasic vascular responses to feeding with early increases in MBV (+36%, P  < 0.008 45 min post feed) reflecting capillary recruitment, and late increases in MFV (+77%, P  < 0.008) and MBF (+130%, P  < 0.007 195 min post feed) reflecting more proximal vessel dilatation. Early MBV responses were synchronized with peak insulin but not increased LBF, while later changes in MFV and MBF occurred with insulin at post absorptive values but alongside increased LBF. All circulatory responses were absent in old men ( N  = 7). Thus, impaired postprandial circulation could impact age‐related declines in muscle glucose disposal, protein anabolism, and muscle mass. Abstract : e00119 Abstract : We developed and validated a method by which to measure muscle microvascular blood flow. In doing this, we demonstrated temporal responses to feeding in youth and aging; in doing so uncovering age‐related deficits in fed state muscle blood flow.